The role of autoimmune processes in the course of mental illness - a review of the most important immunological markers and therapeutic perspectives. - Madoń, Joanna; Czechowicz, Marta; Gadziński, Patryk (Journal of Education, Health and Sport, 2025)
Background A growing body of research indicates that autoimmune processes may play a significant role in the etiopathogenesis of mental disorders common worldwide, including schizophrenia, affective disorders, and depression. Abnormal immune system activation, including elevated levels of proinflammatory cytokines and the presence of autoantibodies, is associated with exacerbated psychopathological symptoms and cognitive decline in some patients. At the same time, research results remain inconclusive due to factors such as the heterogeneity of clinical populations, differences in disease progression, the impact of pharmacological treatment, and varying methods for measuring immune markers. Despite these limitations, autoimmune phenomena represent a promising direction for the search for biomarkers and new therapeutic approaches. Aim This study aims to review the current state of knowledge on the impact of autoimmune processes on the development of psychiatric conditions. Materials and Methods The review includes 27 studies published primarily between 2015 and 2025, selected for their number and relevance to current medical knowledge. Results Research indicates that disturbances in the proper functioning of the immune system, including elevated levels of proinflammatory cytokines, microglial activation, and the presence of autoantibodies, can affect neuronal function, synaptic plasticity, and the integrity of the blood-brain barrier. Although the results of some studies remain uncertain due to methodological differences and clinical heterogeneity, a growing body of evidence suggests that immunological mechanisms may play a significant role in the pathogenesis of mental illness. Conclusions A growing body of research shows that autoimmune processes may influence the development of certain mental illnesses through immune system dysfunction and the resulting inflammation in the central nervous system.